Hearing Loss in Treacher-Collins Syndrome - Fezzan Athama Fuadi; Wijana - (PERHATI-KL, 2021)
Background: Treacher Collins Syndrome (TCS) is a craniofacial disorder that has a dominant autosomal disorder in facial development, found 1 in every 50.000 births. The most often manifestations could be mandibulofacial disorder, microtia, atresia of the ear canal, and hearing loss. This syndrome is also accompanied by bone malformations of the ossicular chain in the middle ear, which can lead to conductive hearing loss up to 50% of cases, besides sensory neural hearing loss. Purpose: To report one case of Treacher Collins syndrome who came to the Audiology-Vestibular Clinic, Dr. Hasan Sadikin General Hospital Bandung. Case report: The patient came with symptoms of micrognathia and microtia with bilateral hearing loss. The right ear is smaller than the left ear, and compliant with 3rd grade microtia. He had undergone reconstruction ear surgery of the right ear, and had an improvement in audiological examination after the second stage of reconstruction. There was TCOF 1 (Treacle Ribosome Biogenesis Factor 1) gene mutation involved in this case. Clinical question: What is the best management for TCS with micrognathia, microtia and severe bilateral hearing impairments? Review method: Literature search was performed with keywords Treacher Collins Syndrome AND microtia AND hearing loss. Result: The search obtained 263 literatures published in the last 10 years, and found 12 articles relevant with the topics. Conclusion: TCS is a rare inherited disorder, but the diagnosis could be easily established. Early intervention with hearing rehabilitation, audio-verbal rehabilitation, and reconstruction ear surgery should be carried out for a better quality of life.ABSTRAK Latar belakang: Sindroma Treacher Collins adalah kelainan kongenital auotosom dominan pada kepala dan wajah, yang ditemukan pada 1 dari 500,000 bayi lahir. Manifestasi yang paling sering didapati adalah kelainan mandibulofasial, mikrotia, atresia liang telinga, dan gangguan pendengaran. Pada sindroma ini terjadi malformasi rangkaian tulang-tulang pendengaran di telinga tengah, yang mengakibatkan tuli konduktif pada 50% kasus, dan dapat juga disertai tuli sensorineural. Tujuan: Melaporkan satu kasus sindroma Treacher Collins yang datang ke poliklinik Audiology-Vestibular, Rumah Sakit Umum Dr. Hasan Sadikin, Bandung. Laporan Kasus: Keluhan utama pasien adalah mikrognatia dan mikrotia disertai gangguan pendengaran kedua telinga. Bentuk telinga kanan lebih kecil daripada telinga kiri, yang sesuai dengan mikrotia derajat 3. Pasien menjalani bedah rekonstruksi telinga kanan, dan memperoleh perbaikan hasil pemeriksaan audiogram pasca tahap kedua bedah rekonstruksi. Pada kasus ini didapati ada mutasi genetik TCOF 1 (Treacle Ribosome Biogenesis Factor 1). Pertanyaan klinis: Bagaimana penatalaksanaan terbaik untuk kasus STC dengan mikrognatia, mikrotia dan gangguan pendengaran berat kedua telinga. Telaah literatur: Penelusuran literatur melalui Google Scholar dilakukan dengan kata kunci Treacher Collins Syndrome DAN microtia DAN hearing loss. Hasil: Didapatkan 263 literatur mengenai STC yang terbit dalam 10 tahun terakhir, dan 12 literatur yang sesuai dengan topik. Kesimpulan: Sindroma Treacher Collins adalah kelainan bawaan langka yang merupakan penyakit keturunan, namun diagnosisnya tidak sulit ditegakkan. Perlu dilakukan intervensi dini berupa rehabilitasi pendengaran, rehabilitasi wicara, dan bedah rekonstruksi telinga untuk memberikan kualitas hidup yang baik bagi penderita.Kata kunci: sindroma Treacher Collins, mikrognatia, mikrotia, gangguan pendengaran